An eXtended Finite Element Method implementation in COMSOL Multiphysics: Solid Mechanics - Jafari, Ahmad; Broumand, Pooyan; Vahab, Mohammad; Khalili, Nasser (Finite elements in analysis and design, 2022)
This paper presents the implementation of the eXtended Finite Element Method (XFEM) in the general-purpose commercial software COMSOL Multiphysics for the first time. An enrichment strategy is proposed, consistent with the structure of the software. To this end, for each set of enrichment functions, an additional Solid Mechanics module is incorporated into the numerical framework, coupled with compatible modifications to the internal variables. The Linear Elastic Fracture Mechanics (LEFM) is exclusively adopted for the crack analysis. The model pre-processing, level set update, stress intensity factor calculation and crack propagation analysis are conducted by employing COMSOL’s built-in features in conjunction with external MATLAB functions through COMSOL LiveLink. All implementational aspects and suggested remedies for the treatment of enriched elements, framework setup, evaluation of stress intensity factors, and numerical integration are described in detail. The accuracy and robustness of the proposed method are examined by several numerical examples, including mixed-mode crack propagation in 2D domains as well as stationary planar fractures in 3D settings. The results represent excellent agreement with available analytical, numerical and experimental observations in the literature. •XFEM implementation in COMSOL Multiphysics is proposed for the first time.•The proposed XFEM enrichment procedure is straight-forward and simple to follow.•The developed model is explored and validated versus a range of benchmark problems.